A pipeline to evaluate inhibitors of the Pseudomonas aeruginosa exotoxin U. Issue 3 (12th February 2021) - Foulkes, Daniel M.; McLean, Keri; Zheng, Yalin; Sarsby, Joscelyn; Haneef, Atikah S.; Fernig, David G.; Winstanley, Craig; Berry, Neil; Kaye, Stephen B.
Abstract : Pseudomonas aeruginosa has recently been highlighted by the World Health Organisation (WHO) as a major threat with high priority for the development of new therapies. In severe P. aeruginosa infections, the phospholipase activity of the type 3 secretion system toxin, ExoU, induces lysis of target host cells and results in the poorest clinical outcomes. We have developed an integrated pipeline to evaluate small molecule inhibitors of ExoU in vitro and in cultured cell models, including a disease-relevant corneal epithelial (HCE-T) scratch and infection model using florescence microscopy and cell viability assays. Compounds Pseudolipasin A, compound A and compound B were effective in vitro inhibitors of ExoU and mitigated P. aeruginosa ExoU-dependent cytotoxicity after infection of HCE-T cells at concentrations as low as 0.5 µM. Addition of the antimicrobial moxifloxacin controlled bacterial load, allowing these assays to be extended from 6 h to 24 h. P. aeruginosa remained cytotoxic to HCE-T cells with moxifloxacin, present at the minimal inhibitory concentration for 24 h, but, when used in combination with either Pseudolipasin A, compound A or compound B, a greater amount of viable cells and scratch healing were observed. Thus, our pipeline provides evidence that ExoU inhibitors could be used in combination with certain antimicrobials as a novel means to treat infections due to ExoU producing P. aeruginosa, as well as the means to identify more potent ExoU inhibitors for future therapeutics.